Uma reflexão sobre o uso do mas em redações de vestibular - Pagnoncelli, Magali (2007)
This qualitative nature research has as objective to analyze the use of but in vestibular contest writings. According to this purpose, we point out, historically, in the first chapter, the vestibular contest and its trajectory and we elucidate why the writing is part of this competition. Starting from this fact, we make a reflection concerning the vestibular contest writing, using it as a textual gender. The second chapter shows a general view on Argumentation Theory in the Language (A.T.L.), developed, initially, by Oswald Ducrot and Jean-Claude Anscombre and, recently, by Ducrot and Marion Carel. The authors defend the thesis that the words have in them an acquired argumentative power orientation in the recurrent contexts, and this orientation will be refuted or reinforced according to the semantic chaining of other words of the speech. Inside this chapter, two sections are distinguished: one that works with the concept of polyphony and approaches some modifications and alterations for which it passed throughout its history; another one shows a semantic study about the use of the articulator but, based on the research of Oswald Ducrot and Carlos Vogt (1979). The third and last chapter aims to the development of the methodology and the analysis of this research corpus, composed by ten writings. In these writings we analyze and verify the ones that shows the use of but while connecting with refutative function and serving to rectify, the ones that shows the use of but as articulator and the other uses of but. This analysis points, from the use of but and on the basis of the polyphonic theory of the enunciation, how the subject holds itself, with which enunciators it identifies itself, and which it rejects or accept. Still, it verifies which the argumentative principle that guides the argumentation made by the author. The writings are part of the 2004 year selection process of the Universidade Regional Integrada URI - Campos de Erechim (Integrated Regional University IRU - Campus of Erechim), where the proposal was: Make a dissertative-argumentative text on the basis of Acquisition of the knowledge